Drawing and Painting in the Training of Future Artists - Charu Sharma (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The article deals with the role of drawing and painting in the system of training specialists in design & art work. The basic educational methods capable of solving this problem in the educational system of higher education are determined. The article describes regular stages in the training of architects and designers. On the basis of practical lessons, the most significant difficulties arising in the process of teaching visual arts are identified. Analysis of practical tasks allowed us to develop an integrated approach to the problem. The practice-oriented integrated approach involves the solution of educational problems, while preserving the historical experience of academic art schools. The study highlights the importance of art disciplines in the training. A number of training methods are analyzed. They are based on the cultural component of traditional Indian education and a unique system of practical research in the art of drawing and painting. Based on the historical method of drawing from nature and the method of painting from nature, as well as the analytical methods, world art plays a crucial role. One of the tasks of the article is to draw attention to the most important issue of development of professional skills and knowledge in visual arts. The study analyzes methods and rules of the use of academic norms, in particular, drawing from nature, whose complete rejection causes a lack of required skills and knowledge when teaching fine arts. This study examines higher education, architecture and analyzes the practical training of future architects.
Keywords: Drawing and Painting; Visual Art; Nature